(3QSGdI aj cdeI GdJhMjOs
(3ChdgG (B:s
(3CeG HYO GdMeO dehdjg hGdSdGI Ydi fHjg hBdg aEfj deG aQZJ ef JgPjH GdQSGdI GdehSheI HGdRhQGA s
(3BNQgG (B:s
(3MaXhG ef cJH GdUhajI cdeGJ eG dge Yde HehGQOgG heTGQYgG Je EQbGe gPg GdQSGdI HYhf Gddg JYGdi GdefGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ MSjf Ydj eMahX (B- (3HZOGO (B(195) s
Keywords: (3GdJhMjO hGdedd hGdfMds